2006
DOI: 10.3310/hta10160
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness and cost-effectiveness of HealOzone® for the treatment of occlusal pit/fissure caries and root caries

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 23 publications
0
47
1
3
Order By: Relevance
“…This finding contradicts a previous study which suggested that the bactericidal effect was the major cause for the caries-inhibitory effect of ozone on occlusal lesions [Brazzelli et al, 2006], although no microbiological investigations had been included in that particular study.…”
Section: Discussioncontrasting
confidence: 56%
“…This finding contradicts a previous study which suggested that the bactericidal effect was the major cause for the caries-inhibitory effect of ozone on occlusal lesions [Brazzelli et al, 2006], although no microbiological investigations had been included in that particular study.…”
Section: Discussioncontrasting
confidence: 56%
“…The hardness values improved significantly in the ozone-treated group after 4, 6 and 8 months compared with baseline, whilst the untreated control group showed no significant improvement. Previous reports on ozone treatment were critically evaluated [1, 7,30]. No published data on the penetration depth of ozone gas into dentinal caries lesions are available.…”
Section: Introductionmentioning
confidence: 99%
“…Heal Ozone remineralizing solution contains xylitol, fluoride, calcium, phosphate and zinc. 16 Giomer: Giomers (Shofu Dental, San Marcos, CA) are the latest category of hybrid restorative materials and they are bioactive as well. Giomer technology represents the true hybridization of glass ionomers and composite resins.…”
Section: Bioactive Restorative Materialsmentioning
confidence: 99%